Photocatalytic deoxygenation of N–O bonds with rhenium complexes: from the reduction of nitrous oxide to pyridine N-oxides. Issue 30 (6th July 2021) - Kjellberg, Marianne; Ohleier, Alexia; Thuéry, Pierre; Nicolas, Emmanuel; Anthore-Dalion, Lucile; Cantat, Thibault
Abstract : A rhenium-based photocatalyst enables the deoxygenation of several compounds containing N–O bonds, such as N2 O and pyridine N -oxides. Abstract : The accumulation of nitrogen oxides in the environment calls for new pathways to interconvert the various oxidation states of nitrogen, and especially their reduction. However, the large spectrum of reduction potentials covered by nitrogen oxides makes it difficult to find general systems capable of efficiently reducing various N -oxides. Here, photocatalysis unlocks high energy species able both to circumvent the inherent low reactivity of the greenhouse gas and oxidant N2 O ( E 0 (N2 O/N2 ) = +1.77 V vs. SHE), and to reduce pyridine N -oxides ( E 1/2 (pyridine N -oxide/pyridine) = −1.04 V vs. SHE). The rhenium complex [Re(4, 4′- t Bu-bpy)(CO)3 Cl] proved to be efficient in performing both reactions under ambient conditions, enabling the deoxygenation of N2 O as well as synthetically relevant and functionalized pyridine N -oxides.